St. Kitts and Nevis : Staff Report for the 2014 Article IV Consultation and the Seventh and Eighth Reviews Under the Stand-by Arrangement and Request for Waivers of Applicability and Nonobservance of Performance Criterion. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2014)
This paper elaborates 2014 Article IV Consultation, Seventh and Eight Reviews Under the Stand-By Arrangement (SBA), and Request for Waivers of Applicability and Non-Observance of Performance Criterion for St. Kitts and Nevis. The discussions focus on strategies to secure sustainable growth through enhancing tourism, developing cost-effective energy sources, and improving the business environment. It states that the authorities' commitment to their program is reflected in the 2014 budget, and their plans to save the bulk of the Citizenship by Investment (CBI) application fees.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet